Exceso de docentes y escasez de maestros. La formación continua: un reto permanente - Huiza Oyola, Humberto (2021)
In teaching we find a series of categories that are not equivalent to each other, even if they are conceived as synonyms. These categories are: instructor, teacher, master and leader. It is crucial to clarify what each of these categories mean in order to avoid confusions and highlight their characteristics and challenges, in order to raise the qualitative level of our national education.